2004
DOI: 10.1590/s1516-31802004000200003
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence of drug prescriptions for elderly and non-elderly inpatients in a teaching hospital

Abstract: CONTEXT: Age-related pharmacokinetic and pharmacodynamic changes have been extensively documented, and several concurrent diseases may underlie multiple drug therapy in the elderly. As a result, the risk of adverse drug reactions and drug interactions increases among aged patients. However, only a few studies have compared the prescribing patterns for different age groups of hospitalized patients or have evaluated the effect of age on drug prescription. OBJECTIVE: To compare the prevalence of drug prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…17 Average number of drugs per prescription was 7 (1050/150) which shows polypharmacy while it was 5.51 (1296/235) in Sharma et al 16 study and 5 in another study in Brazil. 18 The reason for polypharmacy in geriatric patients is coexistence of more than one comorbid conditions. Considering the adverse outcomes associated with polypharmacy, including adverse drug events, drug-drug interactions, increased cost of medications and/or treatment, increased risk of hospitalization, patient nonadherence with treatment (which increases with complex regimens), and various medication errors, we need to take appropriate measures for minimizing polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Average number of drugs per prescription was 7 (1050/150) which shows polypharmacy while it was 5.51 (1296/235) in Sharma et al 16 study and 5 in another study in Brazil. 18 The reason for polypharmacy in geriatric patients is coexistence of more than one comorbid conditions. Considering the adverse outcomes associated with polypharmacy, including adverse drug events, drug-drug interactions, increased cost of medications and/or treatment, increased risk of hospitalization, patient nonadherence with treatment (which increases with complex regimens), and various medication errors, we need to take appropriate measures for minimizing polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…This coincides with the findings of other studies from India, which have also shown highest use of Group A (alimentary and metabolism) drugs according to the ATC classification system. 22 Though it is the most frequently prescribed drug, the prevalence of gastrointestinal 18 has also reported Group A (ranitidine) as one of the most frequently prescribed medicines despite the low prevalence of gastrointestinal conditions. This shows that the irrational use of Group A drugs is common.…”
Section: Discussionmentioning
confidence: 99%
“…Braga et al stated that among inpatients in a teaching hospital, the five most commonly prescribed drugs were dipyrone, ranitidine, metoclopramide, dipyrone in a fixed-dose combination and cefazolin. They also stated that there was a high prevalence of ranitidine prescription (42.9%), but it is noteworthy that only 10.7% had digestive diseases [14]. Additionally, Nidhi et al reported that in an orthopedic department, ranitidine was most frequently prescribed, followed by aspirin, diclofenac sodium and amlodipine [15].…”
Section: Resultsmentioning
confidence: 99%
“…Cruciol-Souza et al, 31 ao avaliarem as prescrições medicamentosas em um hospital universitário brasileiro, detectaram que a metoclopramida estava entre os 10 medicamentos mais prescritos. Braga et al 32 também detectaram fato semelhante: a metoclopramida esteve entre um dos cinco medicamentos mais prescritos em um hospital universitário brasileiro. Observa-se, muitas vezes, que a metoclopramida é prescrita como um medicamento "se necessário", ou seja, apenas se o paciente apresentar náuseas ou vômitos esse medicamento será utilizado.…”
Section: Discussionunclassified